2013
DOI: 10.1007/978-1-62703-748-8_13
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Target and Gene Validation in Viruses and Bacteria

Abstract: Noncoding RNAs (ncRNAs) constitute an evolutionary conserved system involved in the regulation of biological functions at posttranscriptional level. The capability to rapidly adapt their metabolism is essential for the survival of organisms. NcRNAs are a valuable means used by cells to rapidly transfer and internalize an external signal. NcRNAs are capable not only to influence the translational phase but also to affect epigenetic processes. They have been identified in almost all kingdoms of life (from archae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Moreover, studies have confirmed that miRNAs participate in various biological processes, including cell growth, development, proliferation and metabolism, via inhibition of mRNA translation (12,13). Recently, studies revealed that ~20-30% of human genes are regulated by miRNAs, affecting gene expression (14). miR-370 has been suggested to play an inhibition role in many cancers or tumors, including colon cancer and HCC, breast cancer as well as gastric cancer (15).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies have confirmed that miRNAs participate in various biological processes, including cell growth, development, proliferation and metabolism, via inhibition of mRNA translation (12,13). Recently, studies revealed that ~20-30% of human genes are regulated by miRNAs, affecting gene expression (14). miR-370 has been suggested to play an inhibition role in many cancers or tumors, including colon cancer and HCC, breast cancer as well as gastric cancer (15).…”
Section: Introductionmentioning
confidence: 99%
“…This database is very important to researchers who are interested in recombinant enzybiotic design and is available online at http://biotechlab.fudan.edu.cn/database/EnzyBase/home.php. Similar report is available in LAMP database from very similar group of scientists [73][74][75][76].…”
Section: Enzybiotics a New Hope Against Mdr Infectionsmentioning
confidence: 65%
“…Epigenetic modifications may provide an accessory source of fast-acting, reversible, and readily available phenotypic variation that can be directly shaped by both host and pathogen selection pressures ( 33 , 34 ). In this sense, while molecular biologists will focus on identifying and characterizing circumstances where miRNAs are acting as gene regulatory switches, bioinformaticians will have to deal with the prospect that a substantial fraction of all animal mRNAs could have their level of expression influenced by miRNA regulation ( 35 ). The miRNAs has been widely described in various pathological conditions caused by parasites.…”
Section: Discussionmentioning
confidence: 99%